Bibliometric and visualized analysis of metal-organic frameworks in biomedical application - Yu, Sanyang; Xu, Kaihao; Wang, Zhenhua; Zhang, Zhichang; Zhang, Zhongti (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Metal-organic frameworks (MOFs) are hybrid materials composed of metal ions or clusters and organic ligands that spontaneously assemble via coordination bonds to create intramolecular pores, which have recently been widely used in biomedicine due to their porosity, structural, and functional diversity. They are used in biomedical applications, including biosensing, drug delivery, bioimaging, and antimicrobial activities. Our study aims to provide scholars with a comprehensive overview of the research situations, trends, and hotspots in biomedical applications of MOFs through a bibliometric analysis of publications from 2002 to 2022. Methods: On 19 Jan 2023, the Web of Science Core Collection was searched to review and analyze MOF applications in the biomedical field. 3408 studies published between 2002 and 2022 were retrieved and examined, with information such as publication year, country egion, institution, author, journal, references, and keywords. Research hotspots were extracted and analyzed using the Bibliometrix R-Package, VOSviewer, and Citespace. Results: We showed that researchers from 72 countries published articles on MOFs in biomedical applications, with China producing the most publications. The Chinese Academy of Science was the most prolific contributor to these publications among 2,209 institutions that made contributions. Reference co-citation analysis classifies references into 8 clusters: synergistic cancer therapy, efficient photodynamic therapy, metal-organic framework encapsulation, selective fluorescence, luminescent probes, drug delivery, enhanced photodynamic therapy, and metal-organic framework-based nanozymes. Keyword co-occurrence analysis divided keywords into 6 clusters: biosensors, photodynamic therapy, drug delivery, cancer therapy and bioimaging, nanoparticles, and antibacterial. Research frontier keywords were represented by chemodynamic therapy (2020-2022) and hydrogen peroxide (2020-2022). Conclusion: Using bibliometric methods and manual review, this review provides a systematic overview of research on MOFs in biomedical applications, filling an existing gap. The burst keyword analysis revealed that chemodynamic therapy and hydrogen peroxide are the prominent research frontiers and hot spots. MOFs can catalyze Fenton or Fenton-like reactions to generate hydroxyl radicals, making them promising materials for chemodynamic therapy. MOF-based biosensors can detect hydrogen peroxide in various biological samples for diagnosing diseases. MOFs have a wide range of research prospects for biomedical applications.